PRODUCTIVITY OF MAIZE (ZEA MAYS) BASED INTERCROPPING SYSTEM DURING KHARIF SEASON UNDER RED AND LATERITIC TRACT OF WEST BENGAL - M. K. MANDAL,; M. BANERJEE,; H. BANERJEE,; A. ALIPATRA,; G. C. MALIK, (The Bioscan, 2013)
A field experiment was carried out during kharif season of 2010 and 2011 at Sriniketan Research Farm, VisvaBharati, West Bengal. The grain yield and stover yield of maize were significantly higher in case of pure stand of maize than either of its intercropping systems with legumes while the cob yield was highest in the maize with soybean (1:2) intercropping system and it was statistically at par with the yield obtained in sole maize. The grain yield of legume was highest in maize with groundnut intercropping (1:2) and it had highest yield followed by sole groundnut. The maize equivalent yield was highest in maize with soybean intercropping (1:2) followed by maize with groundnut (1:2), maize with groundnut (2:4) and maize with soybean (2:4) intercropping. Thus, under the red and lateritic soil condition where cultivation is practiced with limited water, legume crops like groundnut can be grown as intercrops with maize to get higher monetary returns.